THE EFFECT OF GREEN TRAINING AND DEVELOPMENT IN ENTREPRENEUR PERFORMANCE - Marwah Jasim Kareem (Scholars Digest Publishing, 2024)
This study aims to highlight the impact of green training and development on pioneering performance in the faculties of the University of Baghdad in Iraq. The applied side aimed to determine this effect by analyzing green training and development as an independent variable and pioneering performance as a dependent variable. The field study was used and included a sample of deans, their Assistants, and heads of departments in the faculties of the University of Baghdad, where the sample size was 174 individuals. The data was collected through a questionnaire and analyzed through the statistical analysis program (SPSSv28). The results obtained revealed that the relationship between green training and development and pioneering performance was good and significant.
Keywords: green training and development, entrepreneur performance.